Effect of Intermetallic Phases on Corrosion Initiation of AZ91 Alloy With Rare Earth Y Addition. Issue 5 (May 2015) - Zhang, Li-na; Jia, Ruiling; Li, Dan; Zhang, Wei; Guo, Feng
Abstract : The effect of the rare earth (RE) element Y on the microstructure of AZ91 Mg alloy is investigated. A detailed description of the procedure of identifying the intermetallic phases containing Y in the AZ91 Mg alloy with 0.9 wt% Y addition is presented. The results shows that there are two different kinds of RE phases in scanning electron microscopy (SEM) images. Energy dispersive spectrum (EDS) analysis shows that one is rich in Y element and the other is rich in Mn element. According to the element mapping of electron probe microanalysis (EPMA), the element Al can be found not only in the β-Mg17 Al12 phase but also in these two RE phases. X-ray diffraction (XRD) and transmission electron microscopy (TEM) results further confirm one of the two RE phases is Al2 Y; the phase of Al10 Mn2 Y has just been determined by transmission electron microscopy (TEM) instead of XRD probably because it is scarce. The shapes of these two RE intermetallic phases are pretty similar. The 3D digital microscopy is employed to observe in-situ the effect of the β phase and the above two RE intermetallic phases on the corrosion initiation of the alloys. The results show that the corrosion attack of AZ91 Mg alloy without Y addition starts around the eutectic phase β-Mg17 Al12 . With the addition of 0.9 wt% Y, the two kinds of Y-rich intermetallic phases act as cathodic effect and α phase in the adjacent of them was activated and cathodic effect of the β-Mg17 Al12 phase was inhibited.